Design and Build Mini Alcohol Distillation Equipment from Nira Aren - Yasin Suhartono (International Journal of Mechanical Computational and Manufacturing Research, 2020)
Palm sap is a sweet liquid obtained from the sugar palm plant (Arenga pinnata MEER) by cutting the flower stalk. Generally, palm sap is widely used for the manufacture of brown sugar, fresh drink of palm sap (saguer), vinegar and alcoholic beverages. The model planned for the manufacture of this distillation is water distillation, where the accommodated palm juice is placed in a container that is in direct contact with heating water, then the juice vapor is passed through a pipe which is then condensed through a condenser and the results are accommodated through an alcohol container. over H2O (water) and alcohol, because the difference in boiling temperature where the boiling temperature of water is higher so that at a temperature of 87 C which is the boiling temperature of the alcohol will evaporate first while the water has not undergone the evaporation process. So the pump efficiency is 91.6%. From the results of the calculation of the design of palm juice distalization, the following conclusions can be drawn: Construction of Distalation Capacity: 5 liters Heating media: Stove for kerosene materials Distallation model: Distillation with water, equipped with a condenser Skeleton Material: Iron profile plate 40 Base material: 12 mm plywood board Condenser water tank Size : 300 mm × 300 mm × 300 mm Material : 0.7 mm zinc plate University of North Sumatra.